The Effect of Giving Mindfulnes Based Cognitive Therapy to Reduce Parenting Stress in Parents with Children with CHD (Congenital Heart Disease) - Steven Muhammad Anshor; Dewi Sartika; Fanni Putri Diantina (Green Publisher Indonesia, 2024)
This study aims to determine the effect of Mindfulness Based Cognitive Therapy (MBCT) to reduce parenting stress in parents with children with congenital heart disease (CHD). This study uses a quasi-experimental method with a pre-test-post-test control group design. The participants in this study were 30 parents who had children with congenital heart disease, who were randomly divided into two groups, namely the experimental group and the control group. The experimental group was given MBCT intervention for 8 sessions, while the control group did not get any intervention. Parenting stress measurements were carried out before and after the intervention using the Parenting Stress Index (PSI). The results of the analysis showed that there was a significant difference in parenting stress scores between the experimental group and the control group after being given MBCT intervention (p<0.05). The experimental group experienced a greater decrease in parenting stress scores compared to the control group. The provision of MBCT intervention is effective in reducing parenting stress in parents who have children with congenital heart disease. The results of this study can be considered in the development of psychological interventions to overcome parenting stress in parents with children with CHD